An Adolescents Peer-led Motivational Interviewing Intervention Conducted in Low Socio-Economic Community Youth Organisations to Change Health Risk Behaviours (Smoking, Alcohol and Sedentary Behaviours) - Hickey, Angela Maria (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2024)
Risks and protective factors are associated with health behaviour choices and can have a significant impact on an individuals present and future health outcomes. Engaging in health risk behaviours can contribute to ill health and lead to non-communicable diseases later in life. Adolescence is an important developmental period where health behaviours are established and can have an impact on an individual¿s long-term health and well-being. Adolescents have successfully participated in peer-led health behaviour education programmes to promote health behaviours across various settings. Peers can be effective agents and influence health-promoting (regular physical exercise) and health-compromising (smoking, alcohol consumption) behaviours. Motivational interviewing (MI) is a proven method for health behaviour change and has to manage health-related problems and health risk behaviours. The current Ph.D. presents the findings from a feasibility trial assessing the effectiveness of an adolescent peer-led MI intervention conducted in youth organisations situated in low SES communities.  During this presentation, I will present findings over two phases guided by the Medical Research Council (MRC) on developing, evaluating, and implementing complex health interventions (Craig et al., 2008). The first phase presents qualitative findings from key stakeholders through semi-structured interviews assessing the feasibility of conducting a peer-led MI intervention in low-SES community youth organisations. Qualitative focus groups and semi-structured interviews with adolescent peer educators consider their perspective on participating in MI training and their delivery of weekly MI sessions over a five-week pilot trial. Findings from phase one interviews informed the larger feasibility trial, whereby stakeholder contributions ascertained the acceptability of adopting a peer-led approach, the relevance of the targeted health risk behaviours, and strategies to employ during MI training to capture the engagement of an adolescent cohort. Peer educators provided feedback on training and the intervention process with recommendations for changes in the larger feasibility study. The second phase assessed the efficacy of the intervention through quantitative analysis of peer recipients' behaviour change for self-reported smoking, alcohol use, or physical activity, measured at baseline, six weeks, and three months post-baseline. Participants who attended a health behaviour talk provided a comparative group for one or more behavioural risk factors across the three-time points. Qualitative analysis through semi- structured interviews and focus groups captured the experiences of participants and youth workers assessing the feasibility and acceptability from a youth worker and adolescent (recipient and educator) perspective in implementing the behaviour change intervention within their youth organisation. The intervention was considered feasible, and acceptable, and quantitative analysis of the effectiveness for behavior change produced reductions in alcohol consumption and increases in physical activity for MI recipients at six weeks and three months post-baseline tentatively suggesting maintenance of behaviour change. However, similar reductions were not reported by recipients who chose to decrease their smoking behaviour. Adolescent peer- led MI may present as a method of reducing health-compromising behaviours and increasing healthy behaviours, particularly among those at greatest risk in our society. Further research is warranted to assess and understand the efficacy of this adolescent MI peer-led approach to behaviour change.
APPROVED
Keywords: Peer led; Determinants of health; Motivational Interviewing; Adolescent health; Health Behaviour Change; Feasibility Trial